Platelet-Rich Plasma in Bone Regeneration: Engineering the Delivery for Improved Clinical Efficacy. (23rd June 2014) - Rodriguez, Isaac A.; Growney Kalaf, Emily A.; Bowlin, Gary L.; Sell, Scott A.
Abstract : Human bone is a tissue with a fairly remarkable inherent capacity for regeneration; however, this regenerative capacity has its limitations, and defects larger than a critical size lack the ability to spontaneously heal. As such, the development and clinical translation of effective bone regeneration modalities are paramount. One regenerative medicine approach that is beginning to gain momentum in the clinical setting is the use of platelet-rich plasma (PRP). PRP therapy is essentially a method for concentrating platelets and their intrinsic growth factors to stimulate and accelerate a healing response. While PRP has shown some efficacy in both in vitro and in vivo scenarios, to date its use and delivery have not been optimized for bone regeneration. Issues remain with the effective delivery of the platelet-derived growth factors to a localized site of injury, the activation and temporal release of the growth factors, and the rate of growth factor clearance. This review will briefly describe the physiological principles behind PRP use and then discuss how engineering its method of delivery may ultimately impact its ability to successfully translate to widespread clinical use.